Crow talk : a novel [large type] - Garvin, Eileen (Thorndike Press large print top shelf., 2024)
Frankie O'Neill and Anne Ryan would seem to have nothing in common. Frankie is a lonely ornithologist struggling to salvage her dissertation on the spotted owl following a rift with her advisor. Anne is an Irish musician far from home and family, raising her five-year-old son, Aiden, who refuses to speak. At Beauty Bay, a community of summer homes nestled on the shores of June Lake, in the remote foothills of Mount Adams, it's off-season with most houses shuttered for the fall. But Frankie, adrift, returns to the rundown caretaker's cottage that has been in the hardworking O'Neill family for generations--a beloved place and a constant reminder of the family she has lost. And Anne, in the wake of a tragedy that has disrupted her career and silenced her music, has fled to the neighboring house, a showy summer home owned by her husband's wealthy family. When Frankie finds an injured baby crow in the forest, little does she realize that the charming bird will bring all three lost souls--Frankie, Anne, and Aiden--together on a journey toward hope, healing, and rediscovering joy. Crow Talk is an achingly beautiful story of love, grief, friendship, and the healing power of nature in the darkest of times.